Harsh environmental impact on performance of low voltage underground power cables in hot countries - Alwan, Sabah Hasan (2017)
It is a well-known fact that underground cable loads are affected by many factors such as depth of installation, number of parallel circuits of cables, ambient temperature, conductor size, duct size, size of backfill (or duct bank), and soil thermal resistivity. It is also recognized that resistivity changes with moisture migration under loading conditions. One important factor that is usually ignored is a harsh environment. In hot countries, extreme environmental conditions exist, where the air temperature during the summer season overrides 500C and the dry soil creates very high thermal resistivity. This dissertation takes a direct and comprehensive approach to study the effect of harsh environment on thermal performance of the buried power cables to evaluate the cable temperature rise as well as the effect upon life reduction under constant loading conditions, using the dry zone formulation which provides a simple but consistent framework to model cables and their installed environment. In this thesis, the effect of a harsh environment on the current-carrying capacity (or ampacity) of underground power cables is also presented. The method is given to extend the use of a thermal circuit to cover the entire environment rather than just the cable itself. This is because the nodal solutions in the environment support the prediction of moisture migration in the steady-state adaptation of the two-zone approach to moisture migration employed in the standards, where the native soil surrounding cables is assumed to dry out when the temperature overrides a predefined critical temperature rise above ambient. The main application of the FEM is to predict conductor temperatures in real time from thermal resistivity measurements and a realistic knowledge of the thermal environment of a cable. A full thermal analysis of the installed cable system can lead to high accuracy in the finite element method and predict the conductor temperature from thermal resistivity measurements. The phenomenon of the formation of the dry zone around the cable related to three types of soil is considered, when these types of soil are subjected to constant loading conditions. The IEC-60287 was taken as a reference, while ANSYS software was used to calculate the temperature distribution at the cables with the surrounding environment for different types of native soils with some experimental data. The results have demonstrated that the ambient temperature in Iraq has a direct impact upon cable life temperature and useful life.